If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -21 + -4x = 3x + 16 Reorder the terms: -21 + -4x = 16 + 3x Solving -21 + -4x = 16 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -21 + -4x + -3x = 16 + 3x + -3x Combine like terms: -4x + -3x = -7x -21 + -7x = 16 + 3x + -3x Combine like terms: 3x + -3x = 0 -21 + -7x = 16 + 0 -21 + -7x = 16 Add '21' to each side of the equation. -21 + 21 + -7x = 16 + 21 Combine like terms: -21 + 21 = 0 0 + -7x = 16 + 21 -7x = 16 + 21 Combine like terms: 16 + 21 = 37 -7x = 37 Divide each side by '-7'. x = -5.285714286 Simplifying x = -5.285714286
| 122-5x=10x+22 | | 154-4x=5x+19 | | 0.08x+0.06(x+9)=1.24 | | 5w+1=7(2-3w) | | 1+5x=41+x | | (10x+9)(7x+1)= | | 5x-(x+3)=2x-9 | | 4(m-6)=-2m | | 6b+9=27 | | (7x+1)= | | 3(4+3u)=2(u-1) | | 5x(x+4)(3x+5)=180 | | 4x+6=2y | | 15y-3=8y+4 | | -0.3x+2.1(x-4)=-6.6 | | 12z^2+13z-4=0 | | 65=X*(2x-3) | | -4+2a=12-15a+a | | (10x+9)= | | y=1x+4 | | -3(m-4)+2(5+2m)=29 | | 11h+21=-8h-36 | | -6z=-14 | | 5x=7+11 | | 23z-29=17z+13 | | 5x^2-40x+35=0 | | 3x=0.5x^2+2.5 | | 19f=-12f+56 | | 4x+2(3-2x)=6 | | 37-18+8w=-43 | | 106-7x=20x+22 | | 7m-5=-12 |